2014
DOI: 10.1096/fasebj.28.1_supplement.585.3
|View full text |Cite
|
Sign up to set email alerts
|

High throughput screening of natural products for LDH inhibition as an anti‐mitotic therapeutic target (585.3)

Abstract: A pathological feature hallmark of solid tumors is an over‐functional energy metabolism which results in high level production of lactic acid from glucose. The key enzyme in the production of lactate is LDH, which is highly expressed in tumor tissue and regulates substrate utilization of pyruvate to form lactate. In this study, LDH isolated from human muscle was screened using over 905 plant derived extracts to discover natural products [0.0005‐.77mg/ml] with capability to inhibit LDH. Extracts were tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…flavescens were defatted with n-hexane and extracted with methanol to afford a MeOH extract, which was partitioned between AcOEt, n-BuOH, and H 2 O to give a n-BuOH residue. This extract was subjected to size exclusion and RP-HPLC separations to afford ten new (1-10) and four known compounds (11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…flavescens were defatted with n-hexane and extracted with methanol to afford a MeOH extract, which was partitioned between AcOEt, n-BuOH, and H 2 O to give a n-BuOH residue. This extract was subjected to size exclusion and RP-HPLC separations to afford ten new (1-10) and four known compounds (11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…ABSTRACT: Four new flavonol glycosides (1)(2)(3)(4), two oligosaccharides (5)(6), one α-ionone (7), and three triterpenoid saponins (8)(9)(10), together with four known secondary metabolites (11)(12)(13)(14), were isolated from the aerial parts of Polygala flavescens ssp. flavescens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The changes of normal LDH activity were studied in pervious researches by using different concentrations and substances or oxygen stress (16,17). More recently, natural extracts of commonly used herbs had ability to inhibit LDH subtype A (18) Previous studies showed that the synthesized oxazepine derivatives had high antibacterial activity against E.coli, S.aureus, Salamonella typhii and moderate activity against Klebsiella pneumonia (19). Others showed highest and low bilological activity against S.aureus and no activity against E.coli(20).…”
Section: *The % Inhibition Was Mean Of All Study Samplesmentioning
confidence: 99%